2021
DOI: 10.1021/acs.jpcc.1c01338
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Doped Mesoporous Powders of Hydroxyapatite as Molybdenum-Impregnated Catalysts for Deep Oxidative Desulfurization of Model Fuel: Synthesis and Experimental and Theoretical Studies

Abstract: Mesoporous iron-doped hydroxyapatite (HA) powders with a surface area up to 141 m 2 /g were synthesized and characterized by a variety of analytical and computational approaches, including X-ray diffraction (XRD) and X-ray fluorescence spectroscopy (XRF), atomic emission spectrometry with inductively coupled plasma (AES-ICP), Fourier transform infrared absorption (FTIR), nitrogen adsorption−desorption (BET), scanning and transmission electron microscopy (SEM and TEM), electron paramagnetic resonance (EPR), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 78 publications
(124 reference statements)
1
21
0
Order By: Relevance
“…One of the analytical, non-destructive tools for the investigation of CPs of both biogenic and synthetic origins is electron paramagnetic resonance (EPR) [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The increased sensitivity, spectral and temporal resolution, along with the improved stability of modern commercial EPR spectrometers has opened new possibilities in the study of CPs during the last decade, taking a step towards in situ EPR imaging (EPRI) [44].…”
Section: Introductionmentioning
confidence: 99%
“…One of the analytical, non-destructive tools for the investigation of CPs of both biogenic and synthetic origins is electron paramagnetic resonance (EPR) [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The increased sensitivity, spectral and temporal resolution, along with the improved stability of modern commercial EPR spectrometers has opened new possibilities in the study of CPs during the last decade, taking a step towards in situ EPR imaging (EPRI) [44].…”
Section: Introductionmentioning
confidence: 99%
“…The OHare located within the anion channel, surrounded by calcium ions, and do not largely influence the overall packing and the density of the cell. A similar scheme of charge compensation has been previously considered in Refs [27,28,45].…”
Section: Resultsmentioning
confidence: 98%
“…Accordingly, the synthesis and study of HAp-based catalytic systems with iron impurities have attracted great interest in recent years [21][22][23][24][25][26]. As reviewed by Goldberg et al [27,28], Fe-HAp and Fe oxide nanoparticles demonstrated high efficiency as a catalyst in the field of heavy oil purification via oxidative desulfurization and aquathermolysis methods, oil asphaltene extraction, etc. Besides catalytic applications, Fe-HAp nanoparticles are promising for cancer monitoring [29], as well as magnetic resonance imaging [30], targeted delivery of drugs, and for the treatment of cancer by a hyperthermic method [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations make it possible to determine the most probable substitution position for impurity ions and monitor changes in the unit cell geometry, changes in the local positions of surrounding ions caused by impurities, etc. [20][21][22][23][24][25]. In most cases, DFT calculations help to confirm the assumptions that are made on the basis of experimental data.…”
Section: Introductionmentioning
confidence: 99%